2023
DOI: 10.3389/fphys.2023.1049994
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal serum iron status, hepcidin and interleukin-6 levels in women with preeclampsia

Abstract: Introduction: Preeclampsia can lead to a number of adverse maternal and perinatal effects. The association between iron status [serum iron, ferritin and total iron-binding capacity (TIBC)], unsaturated iron-binding capacity, hepcidin, interleukin-6 (IL-6) levels and preeclampsia is not fully understood.Objective: To assess the levels of iron status, hepcidin and interleukin-6 in women with preeclampsia compared with healthy pregnant women.Method: A case-control study (60 women were recruited in each group) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The disparity in hepcidin and IL-6 levels between the two groups revealed a significant difference (p < 0.05), with the alloimmunization/autoimmunization TDT group exhibiting elevated hepcidin and IL-6 levels compared to the group without alloimmunization/autoimmunization. These findings align with research conducted in Australia and other studies that reported differences and increased levels of hepcidin 19,21,[35][36][37] and IL-6 [38][39][40] in TDT patients compared to NTDT patients. This discrepancy arises from alloantigen stimulation resulting from repeated blood transfusions, showcasing a substantial difference and higher levels in the TDT group.…”
Section: Differences In Hepcidin and Il-6 Levels Among Tdt Patients W...supporting
confidence: 91%
“…The disparity in hepcidin and IL-6 levels between the two groups revealed a significant difference (p < 0.05), with the alloimmunization/autoimmunization TDT group exhibiting elevated hepcidin and IL-6 levels compared to the group without alloimmunization/autoimmunization. These findings align with research conducted in Australia and other studies that reported differences and increased levels of hepcidin 19,21,[35][36][37] and IL-6 [38][39][40] in TDT patients compared to NTDT patients. This discrepancy arises from alloantigen stimulation resulting from repeated blood transfusions, showcasing a substantial difference and higher levels in the TDT group.…”
Section: Differences In Hepcidin and Il-6 Levels Among Tdt Patients W...supporting
confidence: 91%